2020
DOI: 10.1016/j.jbusres.2020.03.021
|View full text |Cite
|
Sign up to set email alerts
|

When interchangeability between providers and users makes a difference: The mediating role of social proximity in collaborative services

Abstract: well as the two anonymous reviewers for their insightful comments and helpful suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 95 publications
2
44
0
4
Order By: Relevance
“…Distrusting strangers can therefore be an essential inhibitor. These results align with some past findings, for example, past studies [2] that identified trust as a critical mediator between interchangeability perceptions and participation in the CE.…”
Section: Inhibitors Of Switchoversupporting
confidence: 92%
See 4 more Smart Citations
“…Distrusting strangers can therefore be an essential inhibitor. These results align with some past findings, for example, past studies [2] that identified trust as a critical mediator between interchangeability perceptions and participation in the CE.…”
Section: Inhibitors Of Switchoversupporting
confidence: 92%
“…They further drew on Philip et al,'s [33,34] studies to differentiate between one-way and two-way users, but without identifying the process that underlies the transition from one-way to two-way users or from a one-way user to a one-way provider. Furthermore, other researchers [2] proposed that the interchangeability feature fosters participation intentions, either as a user or as a provider, or both. In summary, the literature offers emerging themes and theoretical foundations for further research in the user-provider switchover process.…”
Section: Research Backgroundmentioning
confidence: 99%
See 3 more Smart Citations